Epidemiology of diabetic ketoacidosis in Arab patients with type 1 diabetes: a systematic review. Issue 3 (4th February 2016) - Zayed, H.
Summary: Aims: Diabetic ketoacidosis (DKA) is an acute and risky complication of type 1 diabetes. The aim of this study is to build the overall rate of DKA in Arab patients with type 1 diabetes in the 22 Arab nations. This is expected to tailor the healthcare approaches in Arab countries where attention is needed to save lives from the devastating consequences of DKA. Methods: The study here is a quantitative analysis of the articles indexed in four different scientific literature databases: Web of Science, PubMed, Science Direct and Scopus, from inception to June 2015. Arab patients with type 1 diabetes who presented with DKA have been captured. Key information was possible to extract for patients belong to only 12 Arab countries out of the 22 Arab patients. Results: Twenty‐nine studies in 12 different Arab countries captured 4, 688 type 1 diabetes patients with overall rates of 46.7% patients presented with DKA, ranging from a low of 17% in Egypt to a high of 100% in Morocco, Algeria and Tunisia. Conclusion: This is the first descriptive quantitative study to determine the overall DKA rate in 46 years of studies in the Arab world of patients with type 1 diabetes; DKA rates were found to range from 17% to 100% with overall rate of 46.7%.